The 12 bottle bar : a dozen bottles, hundreds of cocktails, a new way to drink - Solmonson, David; Solmonson, Lesley Jacobs (Workman Publishing, 2014)
"It's a system, a tool kit, a recipe book. Beginning with one ... idea--a complete home bar of just 12 key bottles--here's how to make more than 200 classic and unique mixed drinks, including sours, slings, toddies, and highballs, plus [a martini, Manhattan, and mint julep]"--Page 4 of cover.